THE QUALITY OF IRRIGATION WATER ON THE CULTIVATION OF RICE PLANTS (Oryza sativa L.) - Fadlika Mawali; Sofia Wantasen (Jurnal Agroekoteknologi Terapan, 2020)
Water quality is the nature of the water and the content of living beings, substances, energy, or other components in the water. Water quality in general is shown by the quality or the condition of the water that is associated with an activity or specific purposes. Water quality will be different from one activity to another. The quality of the water for purposes of irrigation with different water quality for drinking water purposes. The irrigation water used for agriculture should meet the quality standards of irrigation water according to Government Regulation No. 82 years 2001 is included in class IV so that the quality of irrigation water deserves to be watering for plants. Keywoards:  irrigation; water.  AbstrakKualitas air adalah sifat air dan kandungan makhluk hidup, zat, energi atau komponen lain di dalam air. Kualitas air secara umum ditunjukkan oleh mutu atau kondisi air yang dikaitkan dengan suatu kegiatan atau keperluan tertentu. Kualitas air akan berbeda dari suatu kegiatan ke kegiatan lain. Kualitas air untuk keperluan irigasi berbeda dengan kualitas air untuk keperluan air minum. Air irigasi yang digunakan untuk pertanian sebaiknya memenuhi baku mutu air irigasi sesuai Peraturan Pemerintah Nomor 82 tahun 2001 termasuk dalam kelas IV sehingga kualitas air irigasi layak dijadikan pengairan untuk tanaman. Kata kunci:  irigasi; air.